Un/thinking with Thread/s: Needling Through Boundaries Related to COVID-19 and Medical Training - Mitchell, Veronica (Imaginations, 2021)
This article draws on my connection with sewing threads, and explores how the 2020 Massive Microscopic Sensemaking (MMS) online challenge contributed to an emergent entanglement of timespacemattering related to COVID-19, teaching and researching medical learning in obstetrics, and thinking further with my PhD. It explores affirmative processes enacted during times of anxiety, when my thoughts needled through in-between spaces with different times and materials that were generative and productive. I explain my rhizomatic movements that bleed through conventional separations and boundary-making assumptions. I draw on Karen Barad’s agential realism to theorize the emergence of creative relationalities with artful artifacts enacted with medical undergraduate students, with participants in the MMS project, and with my own PhD during times of tension.